Peran Tokoh Agama Dalam Meningkatkan Kerukunan Umat Beragama di Desa Metro Rejo Kecamatan Buay Madang Timur Kabupaten Oku Timur - Prasitiya, Aning; Darmawan, Candra; Assoburu, Selvia (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "The Role of Religious Figures in Increasing Religious Harmony in Metro Rejo Village, East Buay Madang District, East Oku Regency." Researchers try to reveal the role of religious figures in increasing religious harmony. There are two problem formulations studied. First, what is the role of religious figures in increasing religious harmony? Second, what are the communication strategies of religious figures in increasing religious harmony? The samples in this research were Muslim and Hindu religious leaders as well as the Metro Rejo village head. This research uses descriptive qualitative methods, collecting data through observation, interviews and documentation. In this research, persuasive communication strategy theory is used. The results of the research found that religious leaders had implemented ways of adapting and interacting without differentiating between the race, ethnicity and religion of the community. The role played by religious figures in increasing religious harmony is by directing each congregation to always remind us of God Almighty, giving advice and carrying out religious activities in accordance with their respective beliefs and must respect each other and uphold the value of tolerance. The communication strategy carried out by religious leaders is carrying out activities together, such as cleaning the village environment, creating village facilities and infrastructure and holding deliberations to open up new ideas or thoughts so that when viewed from the perspective of communication between religious communities in Metro Rejo village This communication interaction was successful. This is proven by the people who uphold inter-religious tolerance and always help others regardless of social status, be it a person's race, ethnicity, religion or culture.